Sarbanes-Oxley IT compliance using open source tools, 2E - Lahti, Christian; Peterson, Roderick (Burlington, MA : Syngress, 2007)
The Sarbanes-Oxley Act (officially titled the Public Company Accounting Reform and Investor Protection Act of 2002), signed into law on 30 July 2002 by President Bush, is considered the most significant change to federal securities laws in the United States since the New Deal. It came in the wake of a series of corporate financial scandals, including those affecting Enron, Arthur Andersen, and WorldCom. The law is named after Senator Paul Sarbanes and Representative Michael G. Oxley. It was approved by the House by a vote of 423-3 and by the Senate 99-0. This book illustrates the many Open Source cost-saving opportunities that public companies can explore in their IT enterprise to meet mandatory compliance requirements of the Sarbanes-Oxley act. This book will also demonstrate by example and technical reference both the infrastructure components for Open Source that can be made compliant, and the Open Source tools that can aid in the journey of compliance. Although many books and reference material have been authored on the financial and business side of Sox compliance, very little material is available that directly address the information technology considerations, even less so on how Open Source fits into that discussion. The format of the book will begin each chapter with the IT business and executive considerations of Open Source and SOX compliance. The remaining chapter verbiage will include specific examinations of Open Source applications and tools which relate to the given subject matter, and last a bootable?live? CD will have fully configured running demonstrations of Open Source tools as a valuable technical reference for implementation of the concepts provided in the book * Only book that shows companies how to use Open Source tools to achieve SOX compliance, which dramatically lowers the cost of using proprietary, commercial applications. * Only SOX book with a bootable-Linux CD containing countless applications, forms, and checklists to assist companies in achieving SOX compliance. * Only SOX compliance book specifically detailing steps to achieve SOX compliance for IT Professionals.
Chapter 1: Sox and Cobit Defined -- Chapter 2: Cost of Compliance -- Chapter 3: Why Open Source -- Chapter 4: Domain 1 -- Planning and Organization -- Chapter 5: Domain 2 -- Acquisition and Implementation -- Chapter 6: Domain 3 -- Delivery and Support -- Chapter 7: Domain 4 -- Monitoring -- Chapter 8: The Bottom Line.
Includes index.
Keywords: United States; Auditing, Internal -- Data processing; Information technology -- Management; Open source software; Sarbanes-Oxley Act of 2002 (United States); Electronic books